Some commutativity criteria for 3-prime near-rings - Raji, A. (Algebra and Discrete Mathematics, 2021)
In the present paper, we introduce the notion of *-generalized derivation in near-ring N and investigate some properties involving that of *-generalized derivation of a *-prime near-ring N which forces N to be a commutative ring. Some properties of generalized semiderivations have also been given in the context of 3-prime near-rings. Consequently, some well known results have been generalized. Furthermore, we will give examples to demonstrate that the restrictions imposed on the hypothesis of various results are not superŕuous.